2014
DOI: 10.5137/1019-5149.jtn.10137-13.1
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of ruptured true posterior communicating artery aneurysms

Abstract: AIm: Although true posterior communicating artery (PCoA) aneurysms are rare, they are of vital importance. We reviewed 9 patients with this fatal disease, who were treated with endovascular embolization, and discussed the meaning of endovascular embolization for the treatment of true PCoA aneurysms. mATErIAl and mEThOds: From September 2006 to May 2012, 9 patients with digital substraction angiography (DSA) confirmed true PCoA aneurysms were treated with endovascular embolization. Patients were followed-up wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Only surgical treatment was performed in early cases; however, technical advances achieved in endovascular therapy have permitted the successful treatment of true PCoA aneurysms. 5,6) To preserve perforators of PCoA, direct clipping or intra-aneurysmal embolization is initially considered. In our case, we selected embolization as the aneurysm was large and thrombosed, and we found two disadvantages of the therapy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only surgical treatment was performed in early cases; however, technical advances achieved in endovascular therapy have permitted the successful treatment of true PCoA aneurysms. 5,6) To preserve perforators of PCoA, direct clipping or intra-aneurysmal embolization is initially considered. In our case, we selected embolization as the aneurysm was large and thrombosed, and we found two disadvantages of the therapy.…”
Section: Resultsmentioning
confidence: 99%
“…However, three giant true PCoA aneurysms and less than 10 cases of large true PCoA aneurysms, including our case, have been reported. [3][4][5][6][7] Before the treatment of true PCoA aneurysms, it is necessary to evaluate the distance between the neck of them and ICA or PCA. Most true PCoA aneurysms arise within 2-3 mm from the origin of the PCoA near the ICA.…”
Section: Case Presentationmentioning
confidence: 99%
“…1 The literature on endovascular management of such lesions is limited and the angiographic follow-up rate is considerably lower ( Table 3). [11][12][13][14][15][16][17][18][19] We retrospectively reviewed a series of eight TPCoA aneurysms in our database to assess the safety and efficacy of endovascular treatment in such cases. In this study, most of the treated TPCoA aneurysms were ruptured (7/8, 85.7%).…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, endovascular treatment has been widely used in management of intracranial aneurysms and such strategy in managing TPCoA aneurysms is reported in a few case studies. [11][12][13][14][15][16][17][18][19] Munarriz et al 12 reported a case of successful endovascular coiling of a TPCoA aneurysm with subsequent angiographic stability. Another report from Guo et al 11 showed three such aneurysms, of which two were treated endovascularly without complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation